2012
DOI: 10.1111/j.1360-0443.2012.03868.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of general practitioners in managing alcohol problems: a randomized controlled trial of a tailored improvement programme

Abstract: A tailored, multi-faceted programme aimed at improving general practitioner management of alcohol consumption in their patients failed to show an effect and proved difficult to implement. There remains little evidence to support the use of such an intensive implementation programme to improve the management of harmful and hazardous alcohol consumption in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 41 publications
3
79
0
2
Order By: Relevance
“…15 Therefore, we developed a multifaceted intervention on GPs' behavior toward prevention of hazardous and harmful alcohol consumption, and we conducted a randomized, controlled study to assess its 1-year effects on GPs' screening and advice-giving behavior and its 2-year effects on the level of alcohol consumption of patients. 19 As reported in a previous article, 19 our program did not result in improvement in rates of screening and giving of advice. In this article, we focus on the effect of our program on the level of alcohol consumption of patients.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…15 Therefore, we developed a multifaceted intervention on GPs' behavior toward prevention of hazardous and harmful alcohol consumption, and we conducted a randomized, controlled study to assess its 1-year effects on GPs' screening and advice-giving behavior and its 2-year effects on the level of alcohol consumption of patients. 19 As reported in a previous article, 19 our program did not result in improvement in rates of screening and giving of advice. In this article, we focus on the effect of our program on the level of alcohol consumption of patients.…”
mentioning
confidence: 50%
“…In this article, we focus on the effect of our program on the level of alcohol consumption of patients. When considering the results of the previous article, 19 a significant effect on patient outcome cannot reasonably be expected from our program. We therefore hypothesized that between GPs involved in the intervention program compared with those in the control group there will be no difference in the proportion of patients with hazardous and harmful alcohol consumption who reduced their levels of alcohol consumption to low-risk levels.…”
mentioning
confidence: 89%
“…In addition, six studies reported a combination of professional oriented and organisational oriented implementation strategies, in which in all educational meetings were applied, combined with either changes in medical record systems, formal integration of services or skill mix changes (49-54). Eight studies reported various combinations of professional oriented, organisational oriented, patient oriented and financial oriented strategies (11,23,24,(55)(56)(57)(58)(59).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, SBI is underused with less than 10% of those who might benefit from SBI, receiving a brief intervention (10). Largescale studies that have attempted to increase the uptake of brief interventions have shown that implementing brief interventions in PHC remains difficult (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation